Crisi economiche e mercati finanziari: è di aiuto un nuovo ordine finanziario? (Economic Crises and Financial Markets: Will a New Financial Order Be Helpful?) - Mario Sarcinelli (Moneta e Credito, 2012)
The financial market crises in Japan and the United States due to bubbles and the exchange rate, banking and sometimes foreign debt crises that affected in past years South-East Asia, Russia, Brazil, Argentina, and Turkey made for a brief evaluation of the adequacy of national and international governance mechanisms for preventing and solving them. The widespread dissatisfaction they raise was instrumental in examining whether a larger recourse to finance and risk management is better than macroeconomic management and/or regulation. The types of contract sponsored by Robert J. Shiller in The New Financial Order: Risk in the 21st century have been scrutinised to see whether they offer a better chance to stabilise individual or national income. Even where such an outcome can be secured without aggravating moral hazard, the costs in terms of personal freedom and privacy seem to be particularly high.